Optimizing Instructional Design and Teacher Creativity through a Canva-Based Integrated Platform with Artificial Intelligence Features - Leni Indrawati; Sutrisni Andayani; Siti Nurlaila (Assyfa Learning Journal, 2026)
In the modern educational landscape, rapid digital transformations demand that teachers evolve from passive knowledge consumers into active instructional creators, yet many elementary school teachers still face barriers in effectively integrating artificial intelligence (AI) and creative design into their daily teaching media. This study aims to develop, validate, and evaluate the effectiveness of the Canva-based SIMPADU Portal—an integrated digital education innovation platform designed to systematically foster teachers' pedagogical creativity and digital literacy. Using a Research and Development (R&D) approach patterned after the systematic five-stage ADDIE model (Analyze, Design, Development, Implementation, and Evaluation), the research involved 21 primary school teachers from Lampung as subjects. Data collections were carried out through media and material expert validation checklists, user practicality questionnaires, and pretest-posttest creativity metrics. The development results proved highly robust, achieving an expert validation rate of up to 92.5% for media framework and 90% for material instructional content, alongside an outstanding practicality rating of 86.4%. Furthermore, empirical implementation indicated a significant enhancement in teachers’ performance, yielding an N-Gain score of 0.68 (moderate category), with the most substantial growth observed in idea fluency and media elaboration. It is concluded that the SIMPADU platform serves as a viable, highly practical, and effective digital ecosystem tool to cultivate adaptive learning environments. Future expansion should integrate broader analytical features to sustain long-term teacher professional development